PERAN KEPEMIMIPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN MELALUI MANAJEMEN BERBASIS SEKOLAH - Nizami, Izadri; Marhadi, Hendri; Mustafa , M.Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines how principal leadership contributes to optimizing educational quality through the implementation of School-Based Management (SBM) at SMA YLPI Pekanbaru. Employing a descriptive qualitative approach, data were gathered utilizing observation, in-depth interviews, and documentary analysis. The core focus of this research centers on six pivotal roles of the school principal: educator, manager, administrator, supervisor, leader, and motivator. The findings reveal that the SBM-based strategies designed to elevate educational standards at this institution function highly effectively. This success is demonstrated by the robust collaboration, synergy, and clear communication established among the principal, teaching staff, and administrative personnel in executing their respective duties to attain institutional goals.